Informal Financial Networks: Theory and Evidence - Garmaise, Mark J.; Moskowitz, Tobias J. (Review of Financial Studies, 2003)
We develop a model of informal financial networks and present corroborating evidence by studying the role of property brokers in the U.S. commercial real estate market. Our model demonstrates that service intermediaries, who do not themselves supply loans, can facilitate their clients' access to finance through informal relationships with lenders. Empirically we find that, controlling for endogenous broker selection, hiring a broker strikingly increases the probability of obtaining bank finance. Our results demonstrate that even in the United States, with its well-developed capital markets, informal networks play an important role in controlling access to finance.